1978
DOI: 10.3109/00365527809181774
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Treatment of Acute Experimental Pancreatitis in the Rat

Abstract: Indomethacin given orally or intramuscularly before or shortly after induction of acute sodium-taurocholate or olive-oil-induced pancreatitis in rats reduced the lethality. Neither the enzyme content of serum, ascites, and pancreatic tissue nor the damage to the organ itself were changed under the influence of indomethacin. Thus a modification of systemic effects of acute pancreatitis may be responsible for the beneficial effect of indomethacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 9 publications
1
26
0
1
Order By: Relevance
“…Unfortunately, animal experiments failed to show a beneficial effect of glucagon in acute pancreatitis in rats (Lankisch et al, 1974;Fodor et al, 1975) and dogs (Condon et al, 1974). In controlled studies in man neither glucagon (Durr et al, 1976) nor calcitonin (Goebell, 1976) significantly influenced the course of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, animal experiments failed to show a beneficial effect of glucagon in acute pancreatitis in rats (Lankisch et al, 1974;Fodor et al, 1975) and dogs (Condon et al, 1974). In controlled studies in man neither glucagon (Durr et al, 1976) nor calcitonin (Goebell, 1976) significantly influenced the course of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the degree of necrosis, oedema, and leucocyte infiltration was estimated as absent (0), slight (1), moderate (2), and severe (3) as reported before (Lankisch et al, 1974). The remaining pancreas was used for enzyme assays: ot-amylase (EC321 1) according to Rick and Stegbauer (1970) Ascites (ml) 4-3 ± 1 9 57 2-2 6-3 ± 1 9 56 2-7 4-2 ± 2-1* 6-8 1-3 Necrosis 2-4 2-6 2-2 2-2 3-0 2-6 oedema 2-4 2-3 2-7 2-8 2-8 2-6 leucocyte infiltration 1-2 1.1 0-7 0-6 12; controls n = 11; 0-0 2-5% Na-taurocholatepancreatitis; SRIF-treatment n = 12; controls n = 10;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental acute pancreatitis models, indomethacin was shown to attenuate the severity and lower the mortality (4)(5)(6). Other studies undertaken around the same time, however, showed no beneficial effect (7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However, in laboratory-induced AP in rats, it was demonstrated that long-term aspirin pre-treatment reduced the level of serum inflammatory markers and histological severity of inflammation of pancreatic cells [5]. Another previous study in rats found that indomethacin (a NSAID) administration shortly before and after the onset of AP reduced the severity [10]. In vitro, indomethacin showed effective inhibition of the inflammatory enzyme phospholipase-A2 from AP patients serum [11].…”
Section: Introductionmentioning
confidence: 99%